The histone lysine demethylase JMJD3/KDM6B is recruited to p53 bound promoters and enhancer elements in a p53 dependent manner. - Kristine Williams (Public Library of Science (PLoS), 2014)
The JmjC domain-containing protein JMJD3/KDM6B catalyses the demethylation of H3K27me3 and H3K27me2. JMJD3 appears to be highly regulated at the transcriptional level and is upregulated in response to diverse stimuli such as differentiation inducers and stress signals. Accordingly, JMJD3 has been linked to the regulation of different biological processes such as differentiation of embryonic stem cells, inflammatory responses in macrophages, and induction of cellular senescence via regulation of the INK4A-ARF locus. Here we show here that JMJD3 interacts with the tumour suppressor protein p53. We find that the interaction is dependent on the p53 tetramerization domain. Following DNA damage, JMJD3 is transcriptionally upregulated and by performing genome-wide mapping of JMJD3, we demonstrate that it binds genes involved in basic cellular processes, as well as genes regulating cell cycle, response to stress and apoptosis. Moreover, we find that JMJD3 binding sites show significant overlap with p53 bound promoters and enhancer elements. The binding of JMJD3 to p53 target sites is increased in response to DNA damage, and we demonstrate that the recruitment of JMJD3 to these sites is dependent on p53 expression. Therefore, we propose a model in which JMJD3 is recruited to p53 responsive elements via its interaction with p53 and speculate that JMJD3 could act as a fail-safe mechanism to remove low levels of H3K27me3 and H3K27me2 to allow for efficient acetylation of H3K27.